Seizure Associated Takotsubo Syndrome: A Rare Combination - Htay Htay Kyi; Nour Aljariri Alhesan; Sunil Upadhaya; Samer Al Hadidi (Case Reports in Cardiology)
Takotsubo cardiomyopathy (TC) is increasingly recognized in neurocritical care population especially in postmenopausal females. We are presenting a 61-year-old African American female with past medical history of epilepsy, bipolar disorder, and hypertension who presented with multiple episodes of seizures due to noncompliance with antiepileptic medications. She was on telemetry which showed ST alarm. Electrocardiogram (ECG) was ordered and showed ST elevation in anterolateral leads and troponins were positive. Subsequently Takotsubo cardiomyopathy was diagnosed by left ventriculography findings and absence of angiographic evidence of obstructive coronary artery disease. Echocardiogram showed apical hypokinesia, ejection fraction of 40%, and systolic anterior motion of mitral valve with hyperdynamic left ventricle, in the absence of intracoronary thrombus formation in the angiogram. Electroencephalography showed evidence of generalized tonic-clonic seizure. She was treated with supportive therapy. This case illustrates importance of ECG in all patients with seizure irrespective of cardiac symptoms as TC could be the cause of Sudden Unexpected Death in Epilepsy (SUDEP) and may be underdiagnosed and so undertreated.